Covid-19 and prisons: Reflection on human rights and public health - Ornell, Felipe Rech; Halpern, Silvia Chwartzmann; Scherer, Juliana Nichterwitz; Stock, Barbara Sordi; Camatta, Marcio Wagner; Dotta, Renata Maria; Dalbosco, Carla; von Diemen, Lisia; Kessler, Felix Henrique Paim (Revista de Epidemiologia e Controle de Infecção, 2021)
Background: The epidemic of coronavirus disease 2019 (COVID-19) is a challenging public health problem. The identification of risk groups is essential for the establishment of prevention, screening, containment and treatment strategies. In Brazil, overcrowding and unsanitary conditions in prisons have been a problem for a long time that facilitates infection diseases. Objective: To reflect on the vulnerability of the prison population to COVID-19 and the implications of possible outbreaks in public health Method: Theoretical-reflective study. Results: The prison population has a high clinical vulnerability to contamination by COVID-19. This is aggravated by the structural conditions of prisons, which increases the spread of diseases, especially respiratory conditions, and hinders the establishment of preventive measures. The health care strategies of this population are still insufficient. Conclusion: Outbreaks of COVID-19 in prisons affect prisoners, staff and family members, and could lead the health system to an unprecedented collapse. Strategies to reduce the impact of COVID-19 in prisons and its impact on public health are urgent. Priority health measures, contingency protocols and coordinated actions between the health and justice sectors must be implemented in order to minimize the spread of the virus in this vulnerable and invisible population.